2021
DOI: 10.3390/catal11111359
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Design on the Activity of ZrO2 Catalysts in Cellulose Hydrolysis-Dehydration to Glucose and 5-Hydroxymethylfurfural

Abstract: The one-pot hydrolysis-dehydration of activated microcrystalline cellulose was studied in pure hydrothermal water at 453 K over ZrO2 catalysts produced by thermodegradation, microwave treatment, mechanical activation, and sol–gel methods and spent without any co-catalyst. ZrO2 prepared by microwave treatment was more active compared to ones derived by other methods. The catalyst calcination temperature also impacted reactivity. The cellulose conversion increased simultaneously with acidity and SBET, which in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…At the same time, mesoporous materials with high specific surface area can be obtained by the method of the joint microwave heating of niobia and zirconia precursors. Previously, we reported textural data on pure ZrO2 samples [36]. It was found that oxide catalysts prepared by microwave heating, similar to the present work, had a higher specific surface area compared to catalysts produced by a combination of mechanical activation and microwave.…”
Section: Structural Propertiessupporting
confidence: 87%
See 1 more Smart Citation
“…At the same time, mesoporous materials with high specific surface area can be obtained by the method of the joint microwave heating of niobia and zirconia precursors. Previously, we reported textural data on pure ZrO2 samples [36]. It was found that oxide catalysts prepared by microwave heating, similar to the present work, had a higher specific surface area compared to catalysts produced by a combination of mechanical activation and microwave.…”
Section: Structural Propertiessupporting
confidence: 87%
“…The chromatograph was equipped by a RI detector and Rezex ROA-Organic Acids column (Phenomenex, 300 × 5.0 mm, Torrance, CA, USA). Additional information on catalyst testing techniques can be found in our previous papers [27,36,55].…”
Section: Catalytic Test In a Batch Reactormentioning
confidence: 99%
“…45,46 The solubility constraints of polysaccharides and disaccharides render these carbohydrates unsolvable in traditional solvents, thus making them undesirable feed stocks. 47 Although cellulose and its building unit glucose are the most recognized precursors for the generation of 5-HMF, 48,49 the stout structure of cellulose and the questionable stability of 5-HMF under punitive reaction conditions have been lingering challenges in the conversion of cellulose/glucose to 5-HMF, culminating in poor yields, with acid catalyst-promoted degradation of cellulose/glucose being the norm. 50−52 Heterogeneous acidic catalysts are endowed with several favorable attributes such as lower costs and ease of separation and recycling.…”
Section: ■ Introductionmentioning
confidence: 99%
“…One of the most significant building components based on biomass is 5-hydroxymethylfurfural (5-HMF), which is an important precursor in view of the presence of hydroxymethyl and aldehyde functional groups, and hence is very valuable in the manufacture of polymers, pharmaceuticals, fine chemicals, and related organics. Acid-catalyzed dehydration of polysaccharides, disaccharides, and monosaccharides to furan derivatives is one of the significant pathways. , The solubility constraints of polysaccharides and disaccharides render these carbohydrates unsolvable in traditional solvents, thus making them undesirable feed stocks . Although cellulose and its building unit glucose are the most recognized precursors for the generation of 5-HMF, , the stout structure of cellulose and the questionable stability of 5-HMF under punitive reaction conditions have been lingering challenges in the conversion of cellulose/glucose to 5-HMF, culminating in poor yields, with acid catalyst-promoted degradation of cellulose/glucose being the norm. …”
Section: Introductionmentioning
confidence: 99%